ANTIBACTERIA ASSAY OF PINEAPPLE PEEL (Ananas Comosus L. MERR) MOUTHWASH EXTRACT FORMULA AGAINST Staphylococcus aureus - Helfi Nofita; Eko Mugiyanto; Wulan Agustiningrum (LPPM - Universitas Muhammadiyah Banjarmasin, 2018)
Staphylococcus Aureus is a facultative anaerobes gram-positive bacteria that cause bad breath. Pineapple skin has enzyme bromelin, tannin, chlorine, phenol, which has the suppressing effect of bacterial growth. This aim of this study is to find out and evaluate the best pineapple extract (Ananas Comosus L. Merr) mouthwash preparation formula that meets physical requirements and has the growth inhibition of Staphylococcus Aureus ATCC 25923. Antibacterial activity assay used NA media by agar diffusion method. Physical assay include organoleptic test, pH, viscosity, and cycling test in variation of concentration extract 0,78 g, 1,56 g and 3,12 g. Antibacterial assay showed inhibitories of 1,67 mm, 7,67 mm, 11,33 mm for F1, F2, and F3 respectively with significantly different at p < 0,05.The results show that the F3 has the bigest inhibition growth and meet the physical requirements..